Searching for Peptide Inhibitors of T Regulatory Cell Activity by Targeting Specific Domains of FOXP3 Transcription Factor - Teresa Lozano; Noelia Casares; Celia Martil-Otal; Blanca Anega; Marta Gorraiz; Jonathan Parker; Marta Ruiz; Virginia Belsúe; Antonio Pineda-Lucena; Julen Oyarzabal; Juan José Lasarte (Biomedicines, 2021)
(1) Background: The ability of cancer cells to evade the immune system is due in part to their capacity to induce and recruit T regulatory cells (Tregs) to the tumor microenvironment. Strategies proposed to improve antitumor immunity by depleting Tregs generally lack specificity and raise the possibility of autoimmunity. Therefore, we propose to control Tregs by their functional inactivation rather than depletion. Tregs are characterized by the expression of the Forkhead box protein 3 (FOXP3) transcription factor, which is considered their “master regulator”. Its interaction with DNA is assisted primarily by its interaction with other proteins in the so-called “Foxp3 interactome”, which elicits much of the characteristic Treg cell transcriptional signature. We speculated that the disruption of such a protein complex by using synthetic peptides able to bind Foxp3 might have an impact on the functionality of Treg cells and thus have a therapeutic potential in cancer treatment. (2) Methods: By using a phage-displayed peptide library, or short synthetic peptides encompassing Foxp3 fragments, or by studying the crystal structure of the Foxp3:NFAT complex, we have identified a series of peptides that are able to bind Foxp3 and inhibit Treg activity. (3) Results: We identified some peptides encompassing fragments of the leuzin zipper or the C terminal domain of Foxp3 with the capacity to inhibit Treg activity in vitro. The acetylation/amidation of linear peptides, head-to-tail cyclization, the incorporation of non-natural aminoacids, or the incorporation of cell-penetrating peptide motifs increased in some cases the Foxp3 binding capacity and Treg inhibitory activity of the identified peptides. Some of them have shown antitumoral activity in vivo. (4) Conclusions: Synthetic peptides constitute an alternative to inhibit Foxp3 protein–protein interactions intracellularly and impair Treg immunosuppressive activity. These peptides might be considered as potential hit compounds on the design of new immunotherapeutic approaches against cancer.